Evaluation of the Effectiveness of Intra-operative Low Dose Ketamine Infusion on Post-operative Pain Management Following Major Abdominal Gynaecological Surgeries - IJ, Onyekpa; J, Ogili Jeremiah; U, Odugu Boniface (Jour Med Resh and Health Sci, 2022)
Background: Post-operative pain management has remained a major challenge to most surgeons and patients despite the availability of an array of pharmacologically active agents and techniques. The multimodal approach to post-operative pain management is the current trend in achieving better post-operative analgesia with minimal or no side-effects. The pharmacology of ketamine, its availability, accessibility, cost effectiveness and relative minimal side-effects at low doses, make ketamine a good option in the management of post-operative pain especially in low resource countries like Nigeria. Aim: The aim of the study was to determine the effectiveness of continuous intra-operative infusion of low dose of ketamine at 0.5mg/kg/hr on post operative analgesia following major abdominal gynaecological surgeries Materials & Methods: The study was a prospective, double blinded, and randomized controlled trial carried out in ESUT Teaching Hospital, Enugu following ethical approval by the hospital Ethics Committee. The participants were randomized into two groups: A &B. Group A (fentanyl-ketamine group) received continuous intravenous infusion of 2µg/kg/hr of fentanyl + 0.5mg/kg/hr of ketamine whereas group B (fentanyl-normal saline group) received intravenous infusion of 2µg/kg/hr of fentanyl + normal saline only. All patients had standard monitoring of the blood pressure, oxygen saturation, ECG, end tidal carbon dioxide and temperature peri-operatively. The primary outcome measure was time to first request for analgesia after surgery. Secondary outcome measures were pain scores in the first six and at the twenty fourth hours, post-operative analgesic consumption and the overall satisfaction with pain control. Pain scores were assessed using the numerical rating scale. Data analysis: Data obtained from the study was analyzed using statistical package for social sciences version 22. The data was summarized using proportions, means, and standard deviation and the results presented in tables. Inter-group comparison was done with chi-square test for categorical variables and students t-test for continuous variables. A p-value of less than 0.05 was considered statistically significant. Results: The two groups were compatible with respect to socio-demographic characteristics, duration of surgery and the doses of fentanyl administered intra-operatively. The time to request for analgesia was longer and statistically significant for the ketamine-normal saline group, 71.69±4.54 minutes as against the fentanyl-ketamine group, 33.97±5.28 minutes (t=32.062, p<0.001). Both groups had NRS less than 3 within the first 6 hours post surgery. The NRS pain assessment in the first 6 hours at rest and at deep inspiration showed no statistically significant difference. The worst pain 24 hours was not statistically significant either. The post-operative analgesic (morphine) consumption was lower for fentanyl-ketamine group at all measured points from the 1st to the 24th hour of post-operative period. The reduction in morphine consumption was also statistically significant from the first hour to the 24th hour of post-operative period in the fentanyl-ketamine group. The level of satisfaction with overall pain control was better in the ketamine group (p<0.001). There was no observed statistically significant undesirable effect or complication in either group Conclusion: The administration of intra-operative low dose ketamine infusion with fentanyl to patients during major abdominal gynaecological surgeries enhanced post-operative analgesia and overall satisfaction with pain control. It reduced post-operative analgesic requirements in the immediate post-operative period. There were no significant side-effects or complications.